MINAT PETANI DALAM BERUSAHATANI NILAM DI KELURAHAN TIWORO KECAMATAN TIWORO KEPULAUAN KABUPATEN MUNA BARAT - Syunni Yatun; Musadar Mappasomba; Salahuddin Salahuddin; Tjandra Buana (Universitas Halu Oleo, 2023)
This study aims to: (1) determine the characteristics of farmers in Tiworo Village, Tiworo Islands District, West Muna Regency, (2) determine the interests of farmers in Tiworo Village, Tiworo Islands District, West Muna Regency. The population in this study totaled 20 patchouli farmers who were all taken as respondents (Census). The analysis used in this study is a quantitative analysis using a class interval scale and Spearman's Rank correlation. The results of this study indicate that; (1) Characteristics of farmers in patchouli farming in Tiworo Village, Tiworo Islands District, West Muna Regency, farmers are of productive age, with an average education level of high school and junior high school and the lowest is Elementary School and does not finish school. However, most of the farmers are quite experienced in running their business by having a moderate land area of 0.5-2.0 and the number of family dependents with a moderate family category of 3-4 people. (2) the interest of farmers in trying to cultivate patchouli in Tiworo Village, Tiworo Islands District, West Muna Regency is classified as high.